Does science need bioethicists? Ethics and science collaboration in biomedical research - Kerasidou, Angeliki (Res Ethics, 2014)
Biomedical research is an increasingly multidisciplinary activity bringing together a range of different academic fields and forms of expertise to investigate diseases that are increasingly understood to be complex and multifactorial. Recently the discipline of ethics has been starting to find a place in large-scale biomedical collaborations. In this article we draw from our experience of working with the Malaria Genomic Epidemiology Network (MalariaGEN) and other research projects to reflect upon the integration of ethics into biomedical research. We examine the way in which ethics input may be valuable to research, the forms it tends to take, and also the problems and limitations of such collaborations.